Enrichment of mutant strains after eradication therapy analyzed by gastric wash–based quantitative pyrosequencing - Ritsuko Oikawa; Yoshiyuki Watanabe; Shuichi Miyamoto; Yoshinori Sato; Shoko Ono; Katsuhiro Mabe; Hiroyuki Yamamoto; Mototsugu Kato; Fumio Itoh (Tumor Biology)
The eradication of Helicobacter pylori reduces the risk of gastric cancer. A clear understanding of the factors underlying mixed infection with multiple clarithromycin-susceptible and clarithromycin-resistant H. pylori strains is necessary to design more effective therapies against H. pylori . We aimed to assess how the abundance and prevalence of H. pylori strains vary after clarithromycin-based eradication therapy. Using gastric wash samples, which represent the entire stomach, we sequentially analyzed the abundance and prevalence of H. pylori DNA by 23S ribosomal RNA pyrosequencing before and 1, 2, and 3 years after eradication therapy. Low levels of H. pylori DNA were still detectable at the first-year follow-up in all samples with negative post-treatment urea breath test results. The abundance of H. pylori DNA decreased significantly until the 2-year follow-up, but it switched to an increase at the 3-year follow-up. Importantly, the ratio of the prevalence of mutant strains to the prevalence of wild-type strains had already increased at the first-year follow-up and continued to increase, suggesting the selection and growth of clarithromycin-resistant strains during the follow-up periods. Being sensitive and representative, our assay will be useful in effectively addressing gastric cancer development by enhancing the long-term success of intervention strategies and consecutive surveillance for H. pylori eradication.